Tourism in Sri Lanka during Political, Economic, and Environmental Crises: A Qualitative Analysis - LAKSIRI, W.M. Rohan (Journal of Environmental Management and Tourism, 2025)
This article examines the impact of interconnected political, economic, and environmental crises on Sri Lanka's tourism sector, analyzing their effects on tourism strategies. Employing a qualitative research design, this study uses framework analysis to analyze data collected from semi-structured interviews with tourism stakeholders (for example, hotel managers, tour guides, and government officials) and secondary sources (for example, government reports and policy documents). The study highlights Sri Lanka's tourism industry's vulnerability to political instability, economic downturns, and environmental issues. It emphasizes the need for adaptive strategies like diversifying offerings and targeting new markets. The study underscores the importance of resilience and flexibility in the sector to mitigate future crises. This study fills a gap in literature by conducting a comprehensive analysis of the interconnected challenges confronting Sri Lanka's tourism sector, as well as providing context-specific resilience-building measures tailored to a multifaceted crisis environment. The findings indicate that policymakers should enact specific policies to promote sustainable tourist development, encompassing crisis management, infrastructure enhancement, and environmental preservation. Emphasizing legal systems and advancing sustainable practices will reinstate global confidence in the business.